Respond to this Question
Similar Questions

algebra
Using the equation below as a model, fill in numbers in the place of a and b to create a rational equation that has an extraneous solution. x+a/ax=b/x Part 1. Show all work to solve for x in the equation and check the solution.
asked by rocky on June 9, 2016 
Algebra 1
Solve the equation. Identify any extraneous solutions. sqrt d=6
asked by Help on May 14, 2018 
Math
Solve the equation. Identify any extraneous solutions. x = sqrt root 3x + 40
asked by sharl on May 14, 2011 
Precalculus
Solve (log x)^2 = log x Also, when will their be a possibility that an equation will have an extraneous solution? Like if you got two solutions for a log equation, will a negative solution for x automatically be extraneous?
asked by marcus on November 20, 2012 
Algebra  check to see if correct
5/(y3)=(y+7)/(2y6) i got no solution and i got y=3. Solve each equation. Watch for extraneous solutions.
asked by jackie on March 1, 2009 
algebra
Solve this equation. Identify any extraneous solution. Show all steps. x = [3x + 40]
asked by sharl on May 13, 2011 
CountIblis, can i bother you
Countiblis, i know that you might be busy do you mind if i ask you the following for help.Only if you can please. can you explain to me just one more thing so i can undestand it. Now i have an equation which is : 3x = 3x + 5 which
asked by jasmine20 on January 3, 2007 
ALGEBRA CHECK ANSWERS
Solve each equation by graphing the related function. If the equation has no realnumber solution, write no solution. NOTE: when I write + it has a minus on the bottom too x^2+7=0 a. x= +7 b. x = +3.5 c. x= 0 d. no solution ***
asked by a on April 4, 2017 
MathClarification
Identify any real and extraneous solutions for the equations below. Sqrt p = 1 So, would this have no real or extraneous solutions?
asked by Anonymous on April 28, 2014 
Factoring
What does 3x^33x+2=0 come out to? How would I solve this? Is the x cubed supposed to be x squared? You can compare the equation with the identity: (a+b)^3 = a^3 + 3 a^2 b + 3 a b^2 + b^3 which you can rewrite as: (a + b)^3 = 3 ab
asked by Ace on May 30, 2007